Electronics and coordination engineering of atomic cobalt trapped by oxygen-driven defects for efficient cathode in solar cells. (November 2021) - Jing, Hongyu; Liu, Wei; Zhao, Zhengyan; Zhang, Jiangwei; Zhu, Chao; Shi, Yantao; Wang, Dingsheng; Li, Yadong
Abstract: A rational design and the metal coordination environment regulating of single-atom catalysts (SACs) in specific catalytic reaction remain great challenges. The oxygen defective support can be employed as traps to capture metal species, which provides an effective pathway to synthesize SACs. Here, we propose a counterions-assisted oxygen-driven defect capture (CODC) strategy to fabricate a series of atomically dispersed Co-based catalysts with different electronic and coordination environments. When serving as cathode for dye-sensitized solar cells (DSCs), the triiodine reduction reaction (IRR) activity is very sensitive to the coordination structure. Density functional theory (DFT) calculations reveal that the intrinsic electronic distributions, electron-donating ability, and energy level position determine the coordination behavior and catalytic performance of SACs. Our findings not only define an efficient synthetic strategy to a broad class of M-Nx Cy based SACs for highly-efficient IRR, but also provide an insight for exploring coordination-sensitive reaction from the atomic view. Graphical Abstract: ga1 Highlights: An electronic and coordination environment control for accelerating the IRR process was developed. The atomically dispersed Co-based catalysts were synthesized by a counterions-assisted oxygen-driven defect capture strategy. The IRR catalytic activity was sensitive to the coordination structure of atomic cobalt. The electron-donating ability and energy level position determined the coordination behavior of SACs by DFT study.